Prevention of Hand Eczema among Nurse Apprentice (PREVEDERM): An Interventional Study. Issue 2 (9th February 2021) - Moldovan, Horatiu Remus; Manole, Ionela; Suru, Alina; Butacu, Alexandra-Irina; Tatu, Alin Laurentiu; Lupu, Adriana; Dascalu, Mihai; Tiplica, George-Sorin; Salavastru, Carmen Maria
Abstract: Background: Workers in the healthcare sector are at high risk of developing occupational hand eczema mainly due to frequent exposure to irritants and/or allergens. Amongst workers in healthcare, nurses are at higher risk of developing hand dermatitis. Objectives: To evaluate the effectiveness of a short educational intervention program in preventing occupational hand eczema in nurse apprentices, using two objective tools, namely TEWL and EH, and the HECSI score. Methods: Data regarding professions, wet work exposure, activities performed during working hours, self-reported eczema were collected from 230 nurse students, divided in two study groups: the intervention and the control group (CG). The intervention group (IG) was given education about risks and proper skin care and was provided with cosmeceuticals to be used for skin care during hospital activity. The evaluation of skin properties was performed using questionnaires, HECSI score, measurement of transepidermal water loss (TEWL) and epidermal hydration (EH). Results: A number of 139 apprentice nurses completed the study. Of those participants who completed the study, 19.1% from CG and 19.6% from IG reported, at T1, hand eczema in the last 3 months, while at T2 (3 months later), 59.52 % of the CG and only 11.34 % from the IG stated having eczema in the last 3 months. In the IG, results showed an improvement of CM with 17% and of TEWL with 16%, with only a 0.5% improvement of CM in CG and a marked impairment of TEWL by 33%. Conclusion: Hand eczema is a common occupational dermatosis affecting the medical staff, even during apprenticeship. Early preventive training programs are effective in reducing the burden of occupational contact dermatitis.